Strategi bank syariah mengelola risiko kepatuhan Melalui penerapan kerangka kepatuhan Syariah - Mashudi, Fajar Asnif (Maliki Interdisciplinary Journal, 2025)
Sharia compliance is a fundamental principle that distinguishes Islamic banks from conventional banks. This study aims to analyze the strategies for managing sharia compliance risk, examine the role of the Sharia Supervisory Board (SSB), and evaluate the factors that influence the effectiveness of compliance strategies in Islamic banking. This research employs a library research approach by reviewing relevant academic and practical sources. The findings indicate that effective compliance risk management requires synergy between a comprehensive sharia compliance framework, an active role of the SSB, and the strengthening of internal compliance culture. Moreover, brand image quality and customer trust also contribute to increasing customer loyalty toward Islamic banks. To enhance the effectiveness of compliance strategies, it is necessary to improve human resource capacity—particularly the qualifications of the SSB—strengthen internal supervision systems, and provide continuous education to customers. This study is expected to serve as both a theoretical and practical reference in the development of professional and sustainable sharia compliance risk management.